Proposed soil quality index for rehabilitated forest sites in Malaysia - Karam Singh, Daljit Singh; Abdu, Arifin; Sundara Rajoo, Keeren; Muharam, Farrah Melissa; Mohamad Kasim, Mohamad Roslan; Abdul Hamid, Hazandy (Science Publications, 2016)
A proposed soil quality index named Tropical Soil Quality Index 2 (TSQI2) was developed in this study using statistical analysed data of selected properties (physical, chemical and biological) of composite soil samples collected from natural, secondary and rehabilitated forests of Chikus and Tapah Hill Forest Reserves, Perak, Malaysia. Results of soil evaluation using TSQI2 showed higher values for planted forest in Chikus Forest Reserve compared to those of the rehabilitated forest in Tapah Hill Forest Reserve. Likewise, rehabilitated forest of Tapah Hill Forest Reserve had slightly higher index value compared to that of the secondary forest. The higher index for rehabilitated Chikus Forest Reserve compared to that of the natural forest was due to high MBC/MBN ratio values. The reason for this condition was the lower amount of microbial biomass nitrogen as compared to microbial biomass carbon. Plant growth performance of dominant trees species showed that Shorea leprosula was high in natural forests, followed by rehabilitated forest of Tapah Hill Forest Reserve. The newly proposed TSQI2 (which had been validated using actual data) is suitable for determining the quality of natural and rehabilitated forests in tropical regions.